1985
DOI: 10.1002/pol.1985.170230219
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the surface composition of acrylate copolymer latex films by XPS (ESCA)

Abstract: The interaction of copolymer latex particles with emulsifiers is governed to a great extent by the monomer composition of the particle surface. In this article it is demonstrated that for methylmethacrylate butylacrylate copolymer latexes this quantity, within certain limits, may be determined by XPS (ESCA) by a detailed analysis of the C(1s) line. It is shown that in this analysis secondary shifts in binding energy caused by the two carboxyl‐oxygen atoms have to be taken into account, a fact that has been neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The C1s spectra of bulk PMMA sample are deconvoluted into four components . An XPS fit of the bulk PMMA C1s core level reveals peaks for CCH 3 , CC(O)R, COCO and OCO components.…”
Section: Resultssupporting
confidence: 59%
“…The C1s spectra of bulk PMMA sample are deconvoluted into four components . An XPS fit of the bulk PMMA C1s core level reveals peaks for CCH 3 , CC(O)R, COCO and OCO components.…”
Section: Resultssupporting
confidence: 59%
“…As shown in Figure 7, a nonlinear relationship is exhibited in the Ap variation versus the copolymer composition. However the Ap difference between the two homopolymer latexes is much more larger than with SDS, as is expected when increasing the hydrocarbon chain length of the emulsifier [9], Ap is indeed three times smaller for the P(BuA), whereas a threefold increase is found for the P(VAc), an indication that this more hydrophobic surfactant, would be less compatible with a polar surface than the SDS surfactanc Then, batch and composition-controlled batch were characterized in terms of surface composition (see Table 7 and Fig. 7).…”
Section: B) Adsorption Studies With Shs As Emulsifier Probementioning
confidence: 81%
“…With respect to the surface composition, different methods were succesfully tested for a quantitative determination: (i) the well-known soap titration method [6] which allows us to calculate the molecular adsorption area of an emulsifier at a given polymerwater interface; (ii) estimation of the polarity of latex films by contact angle measurement, as reported by Vijayendran [7] who also established that the surfactant adsorption at a polymer-water interface can be satisfactorily related to the polarity of the polymer surface [8]; (iii) analysis of surface by X-ray photo-electron spectroscopy (XPS or ESCA), as recently shown by Donners et al [9]. The former method has been used for a long time to investigate the effect of many parameters [10][11][12][13][14][15][16][17][18] on the adsorption behavior of an emulsifier such as, for instance, the polarity of the polymer [12,13], the type of emulsifier [15], the partide size [16], the electrolyte concentration [15], the presence of a functional comonomer [14].…”
Section: Introductionmentioning
confidence: 96%
“…Molecular orbital calculations revealed that the BEs of the b-C atoms shift not only because of the change in electronegativity of the substituent F vs. H, but also because of the change in the charge developed on the a-C atoms [5]. The magnitude of this shift is thus expected to be less pronounced as the electronegativity of the substituent decreases, as has been observed in Cl-, Br-, O-, and N-containing polymers [8][9][10][11]. The source of the shifts can be identified using a simple model that describes the BE shifts arising from ground state effects.…”
Section: Introductionmentioning
confidence: 82%